2013
DOI: 10.2147/dddt.s42582
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte-targeting gene transfer mediated by galactosylated poly(ethylene glycol)- graft-polyethylenimine derivative

Abstract: Biscarbamate cross-linked polyethylenimine derivative (PEI-Et) has been reported as a novel nonviral vector for efficient and safe gene transfer in our previous work. However, it had no cell-specificity. To achieve specific delivery of genes to hepatocytes, galactosylated poly(ethylene glycol)-graft-polyethylenimine derivative (GPE) was prepared through modification of PEI-Et with poly(ethylene glycol) and lactobionic acid, bearing a galactose group as a hepatocyte-targeting moiety. The composition of GPE was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…2A). Peaks at 3.5 and 4.5 ppm represented 180 H of PEG (-C H 2 C H 2 O-) and 1H of Gal, respectively [23, 24]. Integration ratios between both peaks at 3.5 and 4.5 ppm were 180.09:1 which confirmed that the molar ratio of PEG:Gal in the PEG-Gal conjugate was (180/180.09):(1/1) ≅ 1:1.…”
Section: Resultsmentioning
confidence: 99%
“…2A). Peaks at 3.5 and 4.5 ppm represented 180 H of PEG (-C H 2 C H 2 O-) and 1H of Gal, respectively [23, 24]. Integration ratios between both peaks at 3.5 and 4.5 ppm were 180.09:1 which confirmed that the molar ratio of PEG:Gal in the PEG-Gal conjugate was (180/180.09):(1/1) ≅ 1:1.…”
Section: Resultsmentioning
confidence: 99%
“…The particle size reached to 65 nm at w/w 3, and then kept relatively constant between 65 nm and 88 nm with polydispersity ranging 0.170–0.338. This size was appropriate for cellular uptake, especially for in vivo hepatocyte transfer, because the majority of fenestrate of the liver sinusoid was smaller than 200 nm in diameter [16]. As for the zeta potential, it was negative when the w/w was 1.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, an in vitro system that takes advantage of ASGPR-mediated endocytosis to transfect hepatocytes with an exogenous DNA using a soluble DNA carrier was developed [56]. Various ASGPR-mediated gene-delivery systems using different polymers have also been described, including galactose-polyethylene glycol (PEG)-poly(L-lysine) [57], galactosylated PEG-graft-polyethylenimine (PEI) [58,59], and galactosylated chitosan-grafted-PEI [60]. In order to attain hepatocyte-specificity and/or improve the efficacy of α-CDE as a genedelivery carrier, Arima et al attached a galactose residue to form Gal-α-CDE (G2) as a novel non-viral carrier [61].…”
Section: Galactosylated α-Cde As a Hepatocyte-selective Pdna Carriermentioning
confidence: 99%